The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1039/c2ra21342g
|View full text |Cite
|
Sign up to set email alerts
|

Progress in redox flow batteries, remaining challenges and their applications in energy storage

Abstract: Redox flow batteries, which have been developed over the last 40 years, are used to store energy on the medium to large scale, particularly in applications such as load levelling, power quality control and facilitating renewable energy deployment. Various electrode materials and cell chemistries have been proposed; some of the successful systems have been demonstrated on a large-scale in the range of 10 kW–10 MW. Enhanced performance is attributable to the improvements in electrodes, separator materials and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
584
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 815 publications
(592 citation statements)
references
References 238 publications
3
584
0
5
Order By: Relevance
“…In addition, the solid-sulphur flow cathode exhibits similar power capability compared with other nonaqueous semi-solid flow chemistries 13,24 , but significantly lower power output compared with the aqueous all-vanadium flow batteries 3,5,26 . The hybrid configuration used in our study limits the scalability of the negative electrode 17 , which can be improved by replacing the lithium metal with semi-solid negative flow catholytes such as the semi-solid silicon anolyte 27 . Our concept of impregnating insulating solid active materials with a conductive carbon network offers a promising direction to further increase the energy density and cycling reversibility of RFBs and semi-solid flow batteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the solid-sulphur flow cathode exhibits similar power capability compared with other nonaqueous semi-solid flow chemistries 13,24 , but significantly lower power output compared with the aqueous all-vanadium flow batteries 3,5,26 . The hybrid configuration used in our study limits the scalability of the negative electrode 17 , which can be improved by replacing the lithium metal with semi-solid negative flow catholytes such as the semi-solid silicon anolyte 27 . Our concept of impregnating insulating solid active materials with a conductive carbon network offers a promising direction to further increase the energy density and cycling reversibility of RFBs and semi-solid flow batteries.…”
Section: Discussionmentioning
confidence: 99%
“…This unique concept creates high cell voltage between the aqueous cathode and the most electronegative alkaline metal. However, the hybrid configuration using lithium metal limits the scalability of energy and power of the lithium-negative electrode 17 , which can be achieved in an all-vanadium flow battery. The authors demonstrated a lithium-ferricyanide flow battery that operates at B3.40 V with a coulombic efficiency 497%.…”
mentioning
confidence: 99%
“…Redox flow batteries (RFBs) have become one of the more promising options for gridscale energy storage [101]. The inert, large surface area electrically conductive support offered to electrocatalysts by RVC led to them being considered as a suitable carbon material in several studies [102], particularly in the case of the soluble lead RFB, but also for the zinc-bromine and vanadium systems.…”
Section: Redox Flow Batteriesmentioning
confidence: 99%
“…[8][9][10][11] Since their advent in the 1970s, 12 numerous aqueous redox chemistries have been developed but none has experienced widespread commercial success. The use of nonaqueous electrolytes in flow batteries is a nascent, yet burgeoning, concept.…”
mentioning
confidence: 99%